Giving to God : Islamic charity in revolutionary times - Mittermaier, Amira, 1974- (University of California Press, 2019)
"During the 2011 uprising, hundreds of thousands of Egyptians took to the streets to call for social justice. Three years later, President el-Sisi promoted economic growth, mega projects, hard work, and citizens' sacrifices. What many of the activists and el-Sisi have in common, despite their radically different visions, is an objection to charity and handouts--to 'giving a man a fish.' Set against this drastically shifting historical backdrop, this book describes an alternative vision of justice: an Islamic ethics of giving that is enacted in Cairo's alleys, mosque courtyards, saint shrines, and slums. It tells the story of a range of pious Muslims--housewives, Sufi devotees, and Salafi volunteers--who, day after day, hand out meals to the poor, and it tells the story of people at the receiving end--beggars, single-parent families, and dervishes. This form of giving is not grounded in compassion, the desire to end poverty, or the hope for a better world, but rather it is understood as a duty and a way to interact with God. By initiating an unlikely conversation between such lived understandings of Islam and the revolutionary moment, this book invites a reimagining of justice and ethics beyond 'the human.' It ethnographically disrupts the entrenched claim that handouts are outdated, shortsighted, and damaging--that they inherently and necessarily stand in the way of social justice"--Provided by publisher.